Skin-feel UV light-curing ink and preparation method and application thereof
By using modified nanomolybdenum disulfide and modified vapor phase silica as touch agents in skin-sensitive UV light curing inks, the problems of ink surface aging and desensitization in the prior art are solved, and good wear resistance and Wear self-repair performance.
Patent Information
- Application Number
- CN202411048968.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-08-01
AI Technical Summary
Existing skin-sensing UV light curing inks are prone to surface aging, decreased touch, sticky and discoloration during long-term use.
Skin-sensing UV composed of 2-6% weight percentage, 20-30% initiator monomer, 1-2% touch-sensing agent, 1-2% functional additive and remaining prepolymer Photocuring inks and improve the wear resistance and wear self-repairing properties of the ink by modifying nanomolybdenum disulfide and modified vapor phase silica as touch agents.
Effectively maintain the skin-feeling performance of the oil film, improve wear resistance and wear self-repairing performance, and avoid surface aging and desensitization.
Smart Images

Figure BDA0004974329450000111 
Figure BDA0004974329450000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of inks, and in particular to a skin-feel UV light-curing ink and a preparation method and application thereof. Background Art
[0002] Ultraviolet (UV) curing ink is an ink material that can quickly cure into a film under ultraviolet light. In recent years, it has been widely used in the fields of printing, coating and intelligent manufacturing. Compared with traditional thermal curing inks, UV curing inks have a faster curing speed, are more environmentally friendly, and have excellent performance of the oil film formed by curing. In addition, adding skin-feel additives to the ink can give the cured oil film a touch that is as gentle as human skin, which can greatly meet consumers' requirements for product appearance and feel.
[0003] Currently, commonly used skin-feel UV light-curing inks mainly include photoinitiators, monomers, prepolymers and additives. Under ultraviolet light, the photoinitiator generates free radicals or cations, which then initiate the polymerization reaction of the monomers and prepolymers to form a cured film. However, the skin-feel UV light-curing inks in the prior art are prone to aging during long-term use, resulting in problems such as decreased touch, surface stickiness and discoloration. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention
[0004] The purpose of the present invention is to provide a skin-feel UV light-curing ink and a preparation method and application thereof, which has good wear resistance and wear self-repairing performance, thereby effectively maintaining the surface skin-feel performance of the oil film.
[0005] The invention provides a skin-feel UV light-curing ink, which comprises the following components by weight percentage: 2-6% of a photoinitiator, 20-30% of an initiating monomer, 1-2% of a touch agent, 1-2% of a functional additive and a balance of a prepolymer; wherein the touch agent comprises modified nano molybdenum disulfide and modified fumed silica in a mass ratio of 1:(0.8-1.2); a preparation method of the modified nano molybdenum disulfide comprises: ultrasonically dispersing the nano molybdenum disulfide in an alkali solution and then separating to obtain an activated powder, ultrasonically dispersing the activated powder with a maleic anhydride solution, and then separating and drying to obtain the modified nano molybdenum disulfide; a preparation method of the modified fumed silica comprises: ultrasonically dispersing the fumed silica in a silane coupling solution and then separating to obtain a gas phase powder, ultrasonically dispersing the gas phase powder in a poly(dimethylsiloxane) solution for reaction, and then separating and drying to obtain the modified fumed silica.
[0006] Optionally, when the nano-molybdenum disulfide is ultrasonically dispersed in an alkaline solution, the alkaline solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, a barium hydroxide solution, and a calcium hydroxide solution.
[0007] Optionally, when the nano-molybdenum disulfide is ultrasonically dispersed in an alkali solution, the solid-liquid mixing ratio of the nano-molybdenum disulfide in the alkali solution is 0.05-0.08 g / mL.
[0008] Optionally, when the nano-molybdenum disulfide is ultrasonically dispersed in an alkaline solution, the average particle size of the nano-molybdenum disulfide is 50-500nm.
[0009] Optionally, when the nano-molybdenum disulfide is ultrasonically dispersed in the alkali solution, the nano-molybdenum disulfide is mixed with the alkali solution and then ultrasonically treated at 20-100 kHz for 10-20 minutes.
[0010] Optionally, when the activated powder and the maleic anhydride solution are ultrasonically dispersed, the mass ratio of the activated powder to the maleic anhydride in the maleic anhydride solution is 1:(0.4-0.6).
[0011] Optionally, when the activated powder is ultrasonically dispersed with the maleic anhydride solution, the solvent of the maleic anhydride solution includes at least one of acetone, chloroform, ethanol, and ether, and the solvent of the maleic anhydride also includes 5-10 vol.% deionized water.
[0012] Optionally, when the activated powder is ultrasonically dispersed with the maleic anhydride solution, the activated powder and the maleic anhydride solution are mixed and then ultrasonically treated at 20-40 kHz for 10-20 min.
[0013] Optionally, when the fumed silica is ultrasonically dispersed in the silane coupling solution, the average particle size of the fumed silica is 7-40 nm.
[0014] Optionally, when the fumed silica is ultrasonically dispersed in the silane coupling solution, the mass ratio of the fumed silica to the silane coupling agent in the silane coupling solution is 1:(0.1-0.2).
[0015] Optionally, when the fumed silica is ultrasonically dispersed in the silane coupling solution, the solid-liquid mixing ratio of the fumed silica in the silane coupling solution is 0.04-0.06 g / mL.
[0016] Optionally, when the fumed silica is ultrasonically dispersed in a silane coupling solution, the silane coupling agent in the silane coupling agent solution includes at least one of trimethylchlorosilane, dimethyldichlorosilane, methyltrichlorosilane, and γ-aminopropyltriethoxysilane.
[0017] Optionally, when the gas phase powder is ultrasonically dispersed in the poly(dimethylsiloxane) solution for reaction, the mass ratio of the gas phase powder to the poly(dimethylsiloxane) in the poly(dimethylsiloxane) solution is 1:(0.3-0.5).
[0018] Optionally, when the gas phase powder is ultrasonically dispersed in the poly(dimethylsiloxane) solution for reaction, the solid-liquid mixing ratio of the gas phase powder in the poly(dimethylsiloxane) solution is 0.02-0.05 g / mL.
[0019] Optionally, when the gas phase powder is ultrasonically dispersed in a poly(dimethylsiloxane) solution for reaction, the solute in the poly(dimethylsiloxane) solution includes at least one of toluene, xylene and carbon tetrachloride.
[0020] Optionally, the anti-wear agent is modified nano molybdenum disulfide and modified fumed silicon dioxide in a mass ratio of 1:1.
[0021] Optionally, the photoinitiator includes at least one of photoinitiator TPO and photoinitiator 819.
[0022] Optionally, the initiating monomer includes at least one of isobornyl acrylate, isobornyl methacrylate, dipropylene glycol diacrylate, and trimethylolpropane triacrylate.
[0023] Optionally, the prepolymer includes at least one of epoxy acrylate, polyurethane acrylate, and polyether acrylate.
[0024] Optionally, the functional additives include a flexible agent, a leveling agent, an antioxidant, a defoaming agent, and a diluent.
[0025] Optionally, the softener includes at least one of polyoxyethylene oleate and monoglycerol fatty acid ester.
[0026] Optionally, the leveling agent includes at least one of Glide 410 and BYK-333.
[0027] Optionally, the antioxidant includes at least one of butylated hydroxyanisole, butylated hydroxytoluene, and tert-butylhydroquinone.
[0028] Optionally, the defoaming agent includes at least one of BYK-024 and Dow Corning DC8628.
[0029] Optionally, the diluent includes at least one of caprolactone acrylate monomer and castor oil-based acrylate.
[0030] In a second aspect, the present invention also provides a method for preparing a skin-feel UV light-curing ink, comprising the following steps: mixing and grinding a photoinitiator, an initiating monomer, a tactile agent, a functional additive and a prepolymer to obtain a skin-feel UV light-curing ink.
[0031] In a third aspect, the present invention also provides an application of a skin-feel UV light-curing ink. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0033] The embodiment of the present invention provides a skin-feel UV light-curing ink, which includes the following components by weight percentage: 2-6% photoinitiator, 20-30% initiator monomer, 1-2% touch agent, 1-2% functional additive and the balance prepolymer.
[0034] In fact, the photoinitiator added to the ink can generate free radicals under ultraviolet light, thereby promoting the polymerization reaction of the initiating monomer and the prepolymer, and realizing the rapid curing of the ink under ultraviolet light. In addition, when the initiating monomer and the prepolymer are polymerized, the initiating monomer can provide cross-linking points, so that the cured film has good flexibility and mechanical strength, and the prepolymer is cured as the main film-forming substance. The touch agent is added to the ink and after curing, it can effectively maintain the smoothness and touch effect of the ink surface.
[0035] Specifically, the touch agent includes modified nano molybdenum disulfide and modified fumed silica in a mass ratio of 1: (0.8-1.2). In fact, the modification of nano molybdenum disulfide and fumed silica can not only effectively improve the compatibility and dispersibility of nano molybdenum disulfide and fumed silica in the ink, but also the fine particles can be evenly dispersed in the ink to form a film, and dispersed in the cured film to improve the mechanical strength and wear resistance of the cured film. In addition, the low friction coefficient of nano molybdenum disulfide itself can form a lubricating layer in the cured film, thereby reducing friction and wear, and when the cured film is worn, the nano molybdenum disulfide and fumed silica can be redistributed to fill the worn area to improve the skin feel retention ability of the cured film surface.
[0036] Specifically, the preparation method of modified nano molybdenum disulfide includes: ultrasonically dispersing nano molybdenum disulfide in an alkali solution and then separating to obtain an activated powder, ultrasonically dispersing the activated powder with a maleic anhydride solution, and then separating and drying to obtain modified nano molybdenum disulfide. In fact, after nano molybdenum disulfide is treated in an alkali solution, not only can the specific surface area of nano molybdenum disulfide be further increased, but also its surface can be hydroxylated to increase the surface active sites, which is conducive to the surface grafting modification of maleic anhydride.
[0037] Specifically, the preparation method of modified fumed silica includes: ultrasonically dispersing fumed silica in a silane coupling solution and then separating to obtain a fumed powder, ultrasonically dispersing the fumed powder in a poly(dimethylsiloxane) solution for reaction, and then separating and drying to obtain the modified fumed silica. In fact, the silane coupling agent can form a stable silicon-oxygen bond on the surface of fumed silica, and the poly(dimethylsiloxane) modification further enhances the lubrication and dispersion properties of fumed silica.
[0038] In some embodiments, when nano-molybdenum disulfide is ultrasonically dispersed in an alkali solution, the alkali solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, a barium hydroxide solution, and a calcium hydroxide solution. In fact, the solute of the alkali solution can be deionized water, and the alkali solution can be a saturated solution, such as a saturated aqueous solution of sodium hydroxide or a saturated aqueous solution of potassium hydroxide.
[0039] In some embodiments, when nano-molybdenum disulfide is ultrasonically dispersed in an alkali solution, the solid-liquid mixing ratio of the nano-molybdenum disulfide in the alkali solution is 0.05-0.08 g / mL. In fact, mixing the nano-molybdenum disulfide with the alkali solution at this solid-liquid ratio is beneficial to improving the dispersibility of the nano-molybdenum disulfide in the alkali solution.
[0040] In some embodiments, when nano-molybdenum disulfide is ultrasonically dispersed in an alkaline solution, the average particle size of the nano-molybdenum disulfide is 50-500 nm. Specifically, the nano-molybdenum disulfide can be a conventional commercial product, for example, the nano-molybdenum disulfide with an average particle size of 50 nm and a specific surface area of 120 m2 produced by Beijing Zhongke Yannuo New Material Technology Co., Ltd. 2 / g of nano molybdenum disulfide.
[0041] In some embodiments, when nano-molybdenum disulfide is ultrasonically dispersed in an alkaline solution, the nano-molybdenum disulfide is mixed with the alkaline solution and then ultrasonically treated at 20-100kHz for 10-20min, which can effectively avoid the agglomeration of the nano-molybdenum disulfide by means of the ultrasonic effect.
[0042] In some embodiments, when the activated powder and the maleic anhydride solution are ultrasonically dispersed, the mass ratio of the activated powder to the maleic anhydride in the maleic anhydride solution is 1:(0.4-0.6). In fact, the solvent of the maleic anhydride solution includes at least one of acetone, chloroform, ethanol, and ether, and the solvent of the maleic anhydride also includes 5-10 vol.% deionized water. Specifically, the maleic acid produced by the hydrolysis of maleic anhydride can react with the hydroxyl group on the surface of the activated powder, thereby improving the grafting modification effect of maleic anhydride.
[0043] In some embodiments, when the activated powder is ultrasonically dispersed with the maleic anhydride solution, the activated powder and the maleic anhydride solution are mixed and then ultrasonically treated at 20-40 kHz for 10-20 min.
[0044] In some embodiments, when the fumed silica is ultrasonically dispersed in the silane coupling solution, the average particle size of the fumed silica is 7-40 nm.
[0045] In fact, the fumed silica can be a conventional commercial product, for example, nano-silica model M-5 which can be purchased from Jinan Yingyu Chemical Co., Ltd.
[0046] In some embodiments, the mass ratio of fumed silica to the silane coupling agent in the silane coupling solution is 1:(0.1-0.2). Specifically, the silane coupling agent includes at least one of trimethylchlorosilane, dimethyldichlorosilane, methyltrichlorosilane, and γ-aminopropyltriethoxysilane.
[0047] In fact, the solid-liquid mixing ratio of fumed silica in the silane coupling solution is 0.04-0.06 g / mL.
[0048] In some embodiments, the mass ratio of the gas phase powder to the poly(dimethylsiloxane) in the poly(dimethylsiloxane) solution is 1:(0.3-0.5), and the solid-liquid mixing ratio of the gas phase powder in the poly(dimethylsiloxane) solution is 0.02-0.05 g / mL.
[0049] In practice, the solute in the poly(dimethylsiloxane) solution includes at least one of toluene, xylene and carbon tetrachloride.
[0050] In some embodiments, the tactile agent is modified nano-molybdenum disulfide and modified fumed silicon dioxide in a mass ratio of 1:1.
[0051] In some embodiments, the photoinitiator includes at least one of photoinitiator TPO and photoinitiator 819; the initiating monomer includes at least one of isobornyl acrylate, isobornyl methacrylate, dipropylene glycol diacrylate, and trimethylolpropane triacrylate.
[0052] In practice, the prepolymer includes at least one of epoxy acrylate, polyurethane acrylate, polyether acrylate.
[0053] In some embodiments, the functional additives include a flexible agent, a leveling agent, an antioxidant, a defoaming agent, and a diluent. Specifically, the flexible agent includes at least one of oleic acid polyoxyethylene ester and glycerol monofatty acid ester; the leveling agent includes at least one of Digo Glide 410 and BYK-333; the antioxidant includes at least one of butylated hydroxyanisole, dibutylhydroxytoluene, and tert-butylhydroquinone; the defoaming agent includes at least one of BYK-024 and Dow Corning DC8628; the diluent includes at least one of acrylic acid caprolactone monomer and castor oil-based acrylate.
[0054] The present invention also provides a method for preparing skin-feel UV light-curing ink, comprising the following steps: mixing and grinding a photoinitiator, an initiating monomer, a tactile agent, a functional additive and a prepolymer to obtain the skin-feel UV light-curing ink.
[0055] Example 1
[0056] Embodiments 1 to 5 of the present invention respectively provide a skin-feel UV light-curing ink, and the components and amounts (mass percentage) used in each embodiment are shown in Table 1 below.
[0057] Table 1 Components and dosages of Examples 1 to 5
[0058] Example 1 Example 2 Example 3 Example 4 Example 5 Photoinitiator 2.3 4.4 5.8 3.7 4.1 Initiator monomer 20 24 30 23 25 Modified Nano Molybdenum Disulfide 0.7 0.6 1 0.7 0.8 Modified fumed silica 0.6 0.5 1 0.6 0.9 Flexibility Agent 0.3 0.2 0.2 0.1 0.4 Leveling agent 0.4 0.3 0.3 0.3 0.2 Antioxidants 0.4 0.5 0.4 0.2 0.3 Defoaming agent 0.2 0.3 0.3 0.3 0.4 Thinner 0.1 0.3 0.3 0.5 0.1 Prepolymer margin margin margin margin margin
[0059] The photoinitiator used in Examples 1 to 5 is photoinitiator 819 (CAS: 162881-26-7), the initiating monomer used is isobornyl acrylate (purchased from Shanghai Hongzhuang Chemical Technology Co., Ltd., CAS: 5888-33-5, IBOA), the flexibilizer used is oleic acid polyoxyethylene ester (purchased from Hai'an Petrochemical Plant, Jiangsu Province, model A-105, CAS: 9004-96-0), the leveling agent used is BYK-333 (purchased from BYK Chemical), the antioxidant used is butylated hydroxyanisole (purchased from Shaanxi Chenming Biotechnology Co., Ltd., CAS: 25013-16-5), the defoamer used is BYK-024 (purchased from BYK Chemical), the diluent used is caprolactone acrylate monomer (purchased from Jiangsu Rayne Environmental Protection Technology Co., Ltd., CAS: 110489-05-9), and the prepolymer used is epoxy acrylate (purchased from Shanghai Zhenli Shi Network Technology Co., Ltd., item number EBECRYL 9636).
[0060] The preparation method of modified nano molybdenum disulfide used in Examples 1 to 5 comprises the following steps: adding nano molybdenum disulfide with an average particle size of 50 nm (purchased from Beijing Zhongke Yannuo New Material Technology Co., Ltd.) into a saturated aqueous solution of sodium hydroxide at a solid-liquid ratio of 0.06 g / mL, ultrasonically treating at a frequency of 40 kHz for 15 minutes, filtering and separating, washing three times with deionized water, and drying to constant weight to obtain an activated powder; mixing the activated powder with a maleic anhydride solution (the solvent in the solution is acetone and water in a volume ratio of 9:1, the mass ratio of the activated powder to maleic anhydride is 1:0.5, and maleic anhydride is purchased from Jinan Aoxing Chemical Co., Ltd.), ultrasonically treating at a frequency of 40 kHz for 15 minutes, filtering and washing three times with deionized water, and drying to constant weight to obtain modified nano molybdenum disulfide.
[0061] The preparation method of the modified fumed silica used in Examples 1 to 5 comprises the following steps: ultrasonically dispersing fumed silica (Jinan Yingyu Chemical Co., Ltd., M-5) having an average particle size of 10 nm in a trimethylchlorosilane ethanol solution (the mass ratio of fumed silica to trimethylchlorosilane is 1:0.1, and trimethylchlorosilane is purchased from Shandong Jinyueyuan New Materials Co., Ltd., CAS: 75-77-4) at a solid-liquid ratio of 0.05 g / mL for 10 minutes, filtering and washing three times with deionized water, and then drying to constant weight to obtain a fumed powder; ultrasonically mixing the fumed powder with a solid-liquid ratio of 0.04 g / mL in a poly(dimethylsiloxane) toluene solution (poly(dimethylsiloxane) is purchased from Jiangsu Rayne Environmental Protection Technology Co., Ltd., CAS: 373-49-9; the mass ratio of the fumed powder to the poly(dimethylsiloxane) is 1:0.5), filtering and washing with deionized water, and drying to constant weight to obtain modified fumed silica.
[0062] The preparation method of the skin-feel UV light-curing ink in Examples 1 to 5 of the present invention comprises the following steps: heating the photoinitiator, initiator monomer, touch agent, functional additive and prepolymer until they are melted, stirring, mixing and grinding to obtain the skin-feel UV light-curing ink.
[0063] Comparative Example 1
[0064] Comparative Example 1 of the present invention provides a skin-feel UV light-curing ink, which is different from Example 3 in that, in Comparative Example 1, modified fumed silica is not added, but 2% of modified nano molybdenum disulfide is added.
[0065] Comparative Example 2
[0066] Comparative Example 2 of the present invention provides a skin-feel UV light-curing ink, which is different from Example 3 in that in Comparative Example 1, no modified fumed silica is added, but 1% fumed silica is added.
[0067] Comparative Example 3
[0068] Comparative Example 3 of the present invention provides a skin-feel UV light-curing ink, which is different from Example 3 in that, in Comparative Example 3, modified nano molybdenum disulfide is not added, but 2% of modified fumed silica is added.
[0069] Comparative Example 4
[0070] Comparative Example 4 of the present invention provides a skin-feel UV light-curing ink, which is different from Example 3 in that, in Comparative Example 4, no modified nano molybdenum disulfide is added, but 1% nano molybdenum disulfide is added.
[0071] Comparative Example 5
[0072] Comparative Example 5 of the present invention provides a skin-feel UV light-curing ink, which is different from Example 3 in that modified nano molybdenum disulfide and modified fumed silica are not added in Comparative Example 5.
[0073] Comparative Example 6
[0074] Comparative Example 6 of the present invention provides a skin-feel UV light-curing ink, which is different from Example 3 in that modified nano molybdenum disulfide and modified fumed silica are not added in Comparative Example 6, but 1% fumed silica and 1% nano molybdenum disulfide are added.
[0075] Performance Testing
[0076] The skin-feel UV light-curing inks prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were printed using a 300-mesh screen printing mesh, and then light-cured using UV or the like, and the following items were tested:
[0077] The cured film was rubbed 100 times with a pressure of 5N using an abrasion tester and then placed at 25°C for 12 days. 10 males aged 20-25 and 10 females aged 20-25 were selected to rate the touch of the cured film before and after rubbing. The subjective rating was performed with surface roughness as 0 and surface velvety feeling as 100. The scores were statistically averaged after removing the highest and lowest scores. The results are shown in Table 2 below.
[0078] After 3M810 tape was pasted on the surface of the cured film for 10 seconds, it was quickly pulled up and the ratio of the area of the cured film adhered to the tape surface to the area of the tape was calculated. The test was repeated five times and the average value was taken. The peeling rate of the cured film was recorded as shown in Table 2 below;
[0079] Acidic sweat was prepared according to the standard described in AATCC TM15-2002, and then the acidic sweat was brushed on the surface of the cured film for corrosion treatment. After being kept at 40°C until dry, the process was repeated 10 times, and then the peeling rate of the cured film was measured using 3M810 tape.
[0080] Table 2 Performance test data
[0081]
[0082]
[0083] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A skin-feel UV light-curing ink, characterized in that: The composition comprises the following components by weight percentage: 2-6% photoinitiator, 20-30% initiator monomer, 1-2% touch agent, 1-2% functional additive and the balance prepolymer; The touch agent includes modified nano molybdenum disulfide and modified fumed silicon dioxide in a mass ratio of 1:(0.8-1.2); The preparation method of the modified nano molybdenum disulfide comprises: ultrasonically dispersing the nano molybdenum disulfide in an alkali solution and then separating to obtain an activated powder; ultrasonically dispersing the activated powder with a maleic anhydride solution, and then separating and drying to obtain the modified nano molybdenum disulfide; The preparation method of the modified fumed silica comprises: ultrasonically dispersing the fumed silica in a silane coupling solution and then separating to obtain a gas phase powder; ultrasonically dispersing the gas phase powder in a poly(dimethylsiloxane) solution for reaction, and then separating and drying to obtain the modified fumed silica; Wherein, when the nano-molybdenum disulfide is ultrasonically dispersed in an alkaline solution, the alkaline solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, a barium hydroxide solution, and a calcium hydroxide solution; The solid-liquid mixing ratio of the nano molybdenum disulfide in the alkali solution is 0.05-0.08 g / mL; The average particle size of the nano molybdenum disulfide is 50-500nm; After mixing the nano-molybdenum disulfide with the alkali solution, ultrasonic treatment is performed at 20-100kHz for 10-20min; When the activated powder and the maleic anhydride solution are ultrasonically dispersed, the method comprises: the mass ratio of the activated powder to the maleic anhydride in the maleic anhydride solution is 1:(0.4-0.6); The solvent of the maleic anhydride solution includes at least one of acetone, chloroform, ethanol, and ether, and the solvent of the maleic anhydride also includes 5-10 vol.% deionized water; After mixing the activated powder with the maleic anhydride solution, ultrasonic treatment was performed at 20-40 kHz for 10-20 min; When the fumed silica is ultrasonically dispersed in the silane coupling solution, the method comprises: the average particle size of the fumed silica is 7-40 nm; The mass ratio of the fumed silica to the silane coupling agent in the silane coupling solution is 1:(0.1-0.2); The solid-liquid mixing ratio of the fumed silica in the silane coupling solution is 0.04-0.06 g / mL; The silane coupling agent in the silane coupling agent solution includes at least one of trimethylchlorosilane, dimethyldichlorosilane, methyltrichlorosilane, and γ-aminopropyltriethoxysilane; When the gas phase powder is ultrasonically dispersed in the poly(dimethylsiloxane) solution for reaction, the method comprises: the mass ratio of the gas phase powder to the poly(dimethylsiloxane) in the poly(dimethylsiloxane) solution is 1:(0.3-0.5); The solid-liquid mixing ratio of the gas phase powder in the poly(dimethylsiloxane) solution is 0.02-0.05 g / mL; The solute in the poly(dimethylsiloxane) solution includes at least one of toluene, xylene and carbon tetrachloride.
2. The skin-feel UV light-curing ink according to claim 1, characterized in that: The touch agent is modified nano molybdenum disulfide and modified fumed silicon dioxide in a mass ratio of 1:
1.
3. The skin-feel UV light-curing ink according to claim 1, characterized in that: The photoinitiator includes at least one of photoinitiator TPO and photoinitiator 819; and / or the initiating monomer includes at least one of isobornyl acrylate, isobornyl methacrylate, dipropylene glycol diacrylate, and trimethylolpropane triacrylate; and / or the prepolymer includes at least one of epoxy acrylate, polyurethane acrylate, and polyether acrylate.
4. The skin-feel UV light-curing ink according to claim 1, characterized in that: The functional additives include a flexible agent, a leveling agent, an antioxidant, a defoaming agent, and a diluent; wherein: the flexible agent includes at least one of oleic acid polyoxyethylene ester and glycerol monofatty acid ester; and / or, the leveling agent includes at least one of Digo Glide 410 and BYK-333; and / or, the antioxidant includes at least one of butylated hydroxyanisole, dibutylhydroxytoluene, and tert-butylhydroquinone; and / or, the defoaming agent includes at least one of BYK-024 and Dow Corning DC8628; and / or, the diluent includes at least one of acrylate caprolactone monomer and castor oil-based acrylate.
5. A method for preparing the skin-feel UV light-curing ink according to any one of claims 1 to 4, characterized in that: The following steps are involved: The skin-feel UV light-curing ink is prepared by mixing and grinding a photoinitiator, an initiating monomer, a touch agent, a functional additive and a prepolymer.
6. Use of the skin-feel UV light-curing ink according to any one of claims 1 to 4.
Citation Information
Patent Citations
Waterproof acid and alkali-resistant flame-retardant insulating power cable material for marine ships
CN105131494A
High-transmittance UV roller coating protective ink and preparation method thereof
CN114231080A
Cited By
High-definition transparent skin-feeling uv gloss, preparation method and application thereof
CN122854914A